REPRESENTATIONS OF TEACHERS: BETWEEN THE PAST AND THE PRESENT - Maria José Coracini (Editora da Universidade de Santa Cruz do Sul, 2015)
This paper aims at discussing the word "representation" in different meanings, mainly in the field of human studies, and to present some images or representations of teachers, which inhabit the professional. These representations result from the analysis of a text presented in the internet. Although, at the end, the author of the text introduces himself as not being a teacher, the representations we can perceive drives to the idea that the teacher is between the past and the present, between traditional representations of a professional, who intends to educate, instruct, and "post-modern" representations of a professional, who needs to adapt himself to the socio-historical moment in which he lives, accepting the school consumerism rules, between the subject of the desire and the subject of the imaginary. The theoretical orientation adopted is constituted by discourse, interwoven with the lacanian psychoanalysis, and the deconstruction, that is named discursive-deconstructionist approach.